Confrontation of women with breast cancer (Research, Society and Development, 2020)
This study aimed to describe the feelings of women with breast cancer; identify ways of coping used by these women; and to point out the strategies that the multidisciplinary team of an oncology center uses to assist these patients. To this end, a descriptive, exploratory study with a qualitative approach was carried out, with 22 women diagnosed with breast cancer and 16 professionals from the oncology sector of a General Hospital who answered a socio-demographic questionnaire and semi-structured interview. It was noticed that the highest incidence rate of breast cancer is among women aged 50 to 69 years, married and with low education, and the trajectory of breast cancer treatment is marked by uncertainties regarding the cure, regarding multiprofessional team highlighted the importance of each professional in alleviating suffering. In view of the analysis, it was possible to argue that, seen by most women as something mutilating and destructive and that totally undermine their self-esteem, breast cancer deserves collective attention to cope with it, where each professional plays his part in alleviating suffering. Given the above, it was possible to conclude that family participation, religion, group therapies, psychological work, welcoming, explanation of treatment, correct prescription by the team and even simple gestures such as listening to the patient, are decisive to assist women in coping with the disease and obtaining a better biopsychosocial adaptation.